2007
DOI: 10.1080/00140130701523611
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of US systems for facial composite production

Abstract: Witness and victims of serious crime are normally requested to construct a facial composite of a suspect's face. While modern systems for constructing composites have been evaluated extensively in the UK, this is not the case in the US. In the current work, two popular computerized systems in the US, FACES and Identikit 2000, were evaluated against a 'reference' system, PRO-fit, where performance is established. In Experiment 1, witnesses constructed a composite with both PRO-fit and FACES using a realistic pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 23 publications
1
39
0
Order By: Relevance
“…In fact, some composites are of such poor quality that they are rarely if ever correctly named (e.g. Frowd et al, 2005aFrowd et al, , 2007c), a situation, as mentioned above, which would lead to low experimental power and ineffective analyses for the current study. We overcame this issue by selecting celebrity images which people had correctly named from previous projects (Frowd et al, 2004(Frowd et al, , 2005b(Frowd et al, , 2007b.…”
Section: Methodsmentioning
confidence: 96%
See 1 more Smart Citation
“…In fact, some composites are of such poor quality that they are rarely if ever correctly named (e.g. Frowd et al, 2005aFrowd et al, , 2007c), a situation, as mentioned above, which would lead to low experimental power and ineffective analyses for the current study. We overcame this issue by selecting celebrity images which people had correctly named from previous projects (Frowd et al, 2004(Frowd et al, , 2005b(Frowd et al, , 2007b.…”
Section: Methodsmentioning
confidence: 96%
“…Frowd et al, 2007c), and so it is sensible to consider experimental power and effect size. The aim was to detect a medium effect size, to be of practical significance, and this was achieved by estimating the number of composites required per condition.…”
Section: Methodsmentioning
confidence: 99%
“…We should acknowledge that changes made to PRO-fit for these studies necessitated using the software differently to how it was originally intended. However, developers of systems using isolated-feature selection (e.g., the FACES system that is popular in the US, Frowd et al, 2007b) should be aware that their software could be usefully improved based on these findings.…”
Section: Discussionmentioning
confidence: 99%
“…The composites produced in this study were unlikely to be of good quality, since the constructors constructed the images themselves rather than with a trained composite-system operator, and so a sensitive measure of composite quality was used (Frowd et al, 2007b): naming participants were shown composites from both context conditions and selected an identity for each from a list of written names corresponding to the identities. This so-called constrained-naming task aimed to facilitate performance.…”
Section: Stage 2: Composite Naming Designmentioning
confidence: 99%
See 1 more Smart Citation